Implementation Of The Think Pair Share Model (Tps) In Improving Learning Outcomes Of Islamic Culture History To Students Of MTSN 1 South Aceh - Edi Saffan; Muhammad Ali Akbar (International Journal of Technology and Education Research, 2023)
The research in this thesis is motivated by a phenomenon in the learning process that exists at MTs Negeri 1 Aceh Selatan , students are weak in mastering and understanding the lessons of Islamic Cultural History . This is because most teachers only use the lecture method when teaching. So that it can cause students to become bored in responding to the lessons delivered by the teacher, and also cause student learning outcomes to decrease in Islamic Cultural History lessons with an average percentage of 58.83% and completeness of student learning outcomes 33.33% in the pre- cycle. The purpose of this study is to increase student activity in class as well as improve student learning outcomes through learning models Think Pair Share (TPS) in Islamic Culture History lessons at MTS Negeri 1 South Aceh . This research uses Class Action Research in two cycles . The subjects of this study were students of class VII I MTS Negeri 1 Aceh Selatan totaling 24 students taken by total sampling in the study. Data collection techniques used are observation, questionnaires and tests. The results showed an increase in student learning outcomes with an average value of 87.38 % . This proves that with the use of learning models Think Pair Share (TPS) in Islamic Culture History lessons can improve student learning outcomes for class VII I MTS Negeri 1 Aceh Selatan . Based on this conclusion, it is suggested to fellow teachers to master and try to apply the latest learning models such as models Think Pair Share (TPS) so that the learning atmosphere can be lively, varied and proven to be effective in increasing learning outcomes